GREEN ACCOUNTING PRACTICES AND THEIR EFFECT ON CORPORATE FINANCIAL PERFORMANCE AND SUSTAINABILITY - Masita Bareut (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the effect of green accounting practices on corporate financial performance and sustainability using a systematic literature review approach. Green accounting is an accounting approach that integrates environmental aspects into financial reporting systems to enhance corporate transparency and accountability. The research method employed is a literature review, examining relevant scholarly articles published over the last ten years (2016–2025). Data were collected from reputable academic journals and analyzed using qualitative content analysis to identify patterns, relationships, and research gaps. The findings indicate that green accounting practices generally have a positive impact on corporate financial performance in the long term, although they may generate additional costs that affect short-term profitability. Furthermore, green accounting plays a significant role in improving corporate sustainability by enabling more effective management of environmental impacts. However, its implementation faces several challenges, including the lack of standardized reporting frameworks, inconsistent disclosure practices, and the risk of greenwashing. This study implies that green accounting is not merely a reporting tool but also a strategic approach for achieving competitive advantage and long-term sustainability. Therefore, stronger support from companies, regulators, and stakeholders is needed to enhance the effectiveness of green accounting implementation.